Evaluation of Okmeydanı within the Framework of Lefebvre’s “Production of Space” Theory - Boşdurmaz, Nurcan; Avcı, Oğulcan (Selim Hilmi Ozkan, 2025)
This study examines the physical, social, and symbolic transformation of Okmeydanı during the Ottoman period in light of Henri Lefebvre's theory of the production of space. The process began with Fatih Sultan Mehmed’s endowment of Okmeydanı for archery and religious rituals after the conquest of Istanbul. Over time, the area evolved to serve various functions, including sacred space, military site, and venue for festivals and feasts. Sultan Mehmed's use of Okmeydanı as an army base during the siege and its designation for prayer and archery after the conquest increased its symbolic and strategic significance. The religious importance of archery in Islam further sanctified the area, strengthened by ritual practices and the placement of range markers by archers. During the reign of Ahmed III, Okmeydanı hosted grand festivals and gradually evolved into a hub for social and sporting events. As firearms gained prominence, Okmeydanı became a military depot and training ground. Despite efforts to preserve the area in the Republican period, Okmeydanı underwent further transformation into a modern space for sports, social activities, and urban settlement. Throughout its history, there has been constant interaction between represented, lived, and representational spaces. In this context, Okmeydanı’s evolution demonstrates how space is continually produced and transformed through social dynamics, preserving its role as a site of memory that intertwines Ottoman religious and military heritage with social relations and ideological representations. © 2025, Selim Hilmi Ozkan. All rights reserved.
Keywords: Archery; Lefebvre; Okmeydanı; Ottoman; Place